Information Technology and Its Role in Revitalizing the Tourism Sector in Iraq - Rasool Salim Maseer (Indonesian Journal of Cultural and Community Development, 2026)
General Background: Tourism is a strategic driver of sustainable development, yet the Iraqi tourism sector faces structural challenges in adapting to digital transformation. Specific Background: This study examines information technology through smart technologies, tourist impression, and tourist experience as determinants of tourism sector revitalization, including serious learning, socialization, stress reduction, and self-development. Knowledge Gap: Limited integration of digital tools in local tourism institutions and insufficient empirical models linking technological dimensions with psychological and social tourism outcomes remain unresolved. Aims: The research aims to analyze the role of information technology in revitalizing the tourism sector in Iraq based on employee perspectives in tourism and travel companies in Baghdad. Results: Using data from 117 valid responses analyzed via SPSS and SmartPLS, findings reveal a strong positive and statistically significant relationship, with information technology explaining 53% of tourism sector revitalization, while smart technologies, tourist impression, and tourist experience all show significant contributions. Novelty: The study presents an integrated applied model connecting technological dimensions with cognitive and social tourism outcomes within a local Iraqi context. Implications: The results highlight the necessity of strengthening digital infrastructure, supporting technology-based tourism services, and adopting e-tourism strategies to improve service quality, tourist satisfaction, and sectoral growth. Highlights: • Strong statistical relationship confirms digital systems as a key driver of tourism recovery• Technological dimensions jointly explain more than half of sector development factors• Employee perceptions indicate high readiness for adopting modern digital practices Keywords: Information Technology, Tourism Sector Revitalization, Smart Technologies, Tourist Experience, E-Tourism